1995
DOI: 10.1007/s001250050422
|View full text |Cite
|
Sign up to set email alerts
|

Impaired tyrosine-kinase activity of muscle insulin receptors from hypomagnesaemic rats

Abstract: SummaryThe effect of magnesium deficiency on glucose disposal, glucose-stimulated insulin secretion and insulin action on skeletal muscle was investigated in rats which were fed a low magnesium-containing diet for 4 days. Control rats were fed a standard diet. Compared to the control rats, the rats fed with low magnesium diet presented: 1) lower serum magnesium levels (0.45 + 0.02 vs 0.78 + 0.01 mmol/1, p < 0.001), 2) higher basal serum glucose (6.8 +__ 0.2 vs 5.5 + 0.2 mmol/1, p < 0.05) and similar basal seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 44 publications
1
40
0
2
Order By: Relevance
“…Briefly, the glucose transporting mechanism, insulin secretion and various enzymes such as synthases and phosphatases depend on Mg in carbohydrate oxidation (16), and Mg also seems to play a vital role in the glucose metabolism in the release of insulin (17), and a role in insulin mediated glucose uptake (18). It has therefore been suggested that Mg deficiency may be involved in the pathogenesis of diabetes (17).…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, the glucose transporting mechanism, insulin secretion and various enzymes such as synthases and phosphatases depend on Mg in carbohydrate oxidation (16), and Mg also seems to play a vital role in the glucose metabolism in the release of insulin (17), and a role in insulin mediated glucose uptake (18). It has therefore been suggested that Mg deficiency may be involved in the pathogenesis of diabetes (17).…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that autophosphorylation of the beta-subunit of the insulin receptor was significantly reduced by 50% in magnesium-deficient rats and the tyrosine kinase activity of insulin receptors by hypomagnesaemia 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Mg depletion provoked a deleterious effect on glucose metabolism due to an impairment of both insulin secretion and action [50]. The IR observed in the skeletal muscles of Mgdeficient rats was linked, at least in part, to a defective tyrosine kinase activity of insulin receptors [51].…”
Section: Magnesium Glucose Intolerance Insulin Resistance and Diabmentioning
confidence: 99%